As relações afetivas no processo de formação continuada de professores - Moraes, Daiane Cristini (2018)
This study aimed to investigate the affective manifestations ways which appear during the teachers’ formation process, identifying if the teacher realizes the role of the affective relationships in the teaching-learning process and pointing formative strategies which may contribute for the teacher being aware of the implications that the affective relationships have on the education. It is a qualitative research which used the Critical Incident technique as a tool for the data production, which was applied to 19 teachers who participate of the continuing formation process offered for the effective teachers from the Municipal Education System of São Paulo. In order to develop the analysis, the affective manifestations presented to the teachers using the Critical Incidents were highlighted and the theoretical support from the literature came mainly from: Almeida; Freire; Leite; Mahoney; and Placco. This investigation brings us evidence of the teachers – research subjects – realizing the affectivity importance in the teaching-learning process. However, they do not get held themselves responsible for the consequences of a work in which the affectivity is present through negative manifestations, conferring to the students the responsibility for the school failure. And, at the same time, they contradict themselves and assume to be unable of transforming the reality presented by the Critical Incidents through changes in the pedagogical practices, indicating the need of investments on continuing education focused on this theme. One may still deduce fragilities in the Pedagogical Coordinator’s role, identified as a conflict mediator, but not well recognized as a mediator in the formative process. The research offers indications of formative needs and changes of practices and viewpoints, in which the affectivity may gain new means. The vision, the active listening and the message in the first person have to be rescued e worked, considering that affectivity may also be learnt